Rice resistance to stem borer. II. Evaluation through larvae feeding on artificial diets containing aqueous plant extracts - Martins, José Francisco da Silva; Parra, José Roberto Postali; Mihsfeldt, Laila Herta (Pesquisa Agropecuaria Brasileira, 2014)
This research was conducted to determine whether antibiosis type resistance in rice to Diatraea saccharalis is associated with biophysical or biochemical factors of the plants. The method to compare insect larval growth in intact plants of resistant and susceptible varieties to growth in artificial diets containing aqueous extracts of the same plants was used. The larval growth in diets was assessed through the nutritional indexes: approximate digestibilily (AD), efficiency of conversion of ingested food (ECI) and digested food (ECD). The method makes it possible to determine if detected antibiosis in some varieties was associated with both biophysical and biochemical plant factors. In Artificial diets, the role of the plant biophysical factors was eliminated, but, some effect of plant chemical composition was maintained. The ECD was the nutritional index which best explained the effect of the chemical composition on larval growth. It was concluded that on varieties where larval growth is high, on intact plants and artificial diets, the plant biophysical and biochemical factors are favorable to the insect. In varieties that are insect-unfavorable in the form of intact plant, but favorable in artificial diet, the antibiosis was considered to be of biophysical nature. ln varieties unfavorable in both forms, antibiosis was considered to be at least of biochemical nature, but the possibility of adverse effect of biophysical factors of the intact plant can not be eliminated.